Immune imbalance underlying depressive symptoms in COPD patients: a study based on BDNF, PD-1, MMP-9, and inflammatory cytokines - Liu, Shanshan; Dong, Jian; Huang, Weiqi; Yan, Jing (Frontiers in Medicine, 2025)
ObjectiveChronic obstructive pulmonary disease (COPD) is frequently accompanied by a high prevalence of depressive symptoms, particularly during acute exacerbations (AECOPD). However, the immunoinflammatory mechanisms underlying AECOPD-associated depression remain poorly elucidated. This study aimed to investigate the potential roles of brain-derived neurotrophic factor (BDNF), programmed cell death protein 1 (PD-1), matrix metalloproteinase-9 (MMP-9), and key inflammatory cytokines—interleukin-1β (IL-1β), interleukin-10 (IL-10), and tumor necrosis factor-α (TNF-α)—in mediating depressive symptoms among hospitalized AECOPD patients. The findings aim to clarify the contribution of immune dysregulation to the development of depression in this population.MethodsA total of 140 patients hospitalized for AECOPD and 50 age- and sex-matched healthy controls were recruited. Patients were stratified into depressive (HAMD ≥ 17) and non-depressive (HAMD < 17) groups based on the Hamilton Depression Rating Scale. Following a 90-day follow-up, patients were further categorized into stable and recurrent exacerbation subgroups. Serum levels of BDNF, PD-1, MMP-9, IL-1β, IL-10, and TNF-α were measured using peripheral blood samples. Intergroup comparisons were conducted, and correlations between biomarker levels and depression severity were analyzed. Multivariate logistic regression was performed to identify independent risk and protective factors for depressive symptoms.ResultsCompared with healthy controls, AECOPD patients showed significantly reduced BDNF levels (0.225 vs. 0.575, p < 0.001) and elevated PD-1 levels (0.865 vs. 0.255, p < 0.001). Within the patient cohort, individuals with depressive symptoms exhibited lower BDNF (0.13 vs. 0.24, p < 0.001) and higher PD-1 expression (0.89 vs. 0.78, p < 0.001) than those without depression. Multivariate analysis identified PD-1 (OR = 3.32) and MMP-9 (OR = 2.18) as independent risk factors for depression, while IL-10 (OR = 0.62) and BDNF (OR = 0.12) emerged as protective factors. Smoking status was also recognized as a modifiable risk factor (OR = 1.73).ConclusionDepressive symptoms in AECOPD patients appear to be driven by a multifaceted interplay involving neuroinflammation (characterized by BDNF reduction and elevated IL-1β/TNF-α), immune dysregulation (marked by PD-1 upregulation and IL-10 suppression), and extracellular matrix remodeling (via increased MMP-9). Modulation of the PD-1/MMP-9 axis may offer a novel therapeutic strategy, while smoking cessation could potentiate BDNF-related neuroprotective effects.